Higher diversity of vegetable consumption is associated with less airway inflammation and prevalence of asthma in school‐aged children. Issue 5 (20th March 2021) - Mendes, Francisca de Castro; Paciência, Inês; Cavaleiro Rufo, João; Farraia, Mariana; Silva, Diana; Padrão, Patrícia; Delgado, Luís; Garcia‐Larsen, Vanessa; Moreira, André; Moreira, Pedro
Abstract: Background: A diet rich in fruits and vegetables has been suggested to counteract the oxidative stress and inflammation that characterize asthma. We aimed to assess the association between vegetable and fruit diversity consumption and asthma and its related outcomes in school‐aged children. Methods: Participants included 647 children (49% females, aged 7‐12 years) recruited from 20 public schools across the city of Porto, in Portugal. Vegetable intake and fruit intake were ascertained using a single self‐reported 24‐hour recall questionnaire. A diversity score was built taking into account the different number of individual vegetables and fruits consumed and categorized into two groups based on the total reported median consumption, which was rounded to the nearest whole number (≤ 3 and >3, for vegetables; and ≤1 and >1, for fruits). A questionnaire was used to enquire about self‐reported medical diagnosis of asthma and respiratory symptoms. Airway inflammation was assessed measuring exhaled fractional nitric oxide concentration (eNO) and was categorized into two groups (<35 and ≥35 ppb). The association between fruit and vegetable diversity and respiratory outcomes was examined using logistic regression models, adjusting for confounders. Results: A higher vegetable diversity consumption per day was negatively associated with having self‐reported asthma (OR = 0.67; 95% CI 0.47, 0.95), while having a vegetable diversity consumption superior to 3 items per day was negatively associated with levels of eNO ≥ 35 ppb (OR = 0.38; 95% CI 0.16, 0.88) and breathing difficulties (OR = 0.39; 95% CI 0.16, 0.97). Conclusion: Eating a greater variety of vegetables was associated with a lower chance of airway inflammation and prevalence of self‐reported asthma in school children. Abstract :